The Impact of Consulting Services on an Auditor’s Independence – A Survey Study on Audit Firms in Lebanon - الموسوي, حسان; زرير, رانيا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
As a result of the knowledge and experience they have, in addition to auditing financial statements for enterprises, auditors sometimes provide consulting services (non-audit services). Some of these services might impair the auditors’ independence with regard to the enterprises. This study aims to identify the role of Lebanese audit firms in providing such consulting services and their impact on the Lebanese auditors’ code of professional conduct. A well-structured questionnaire of three main domains was used to collect data. The samples were all members of Lebanese Association of Certified Public Accountants. The results of the study showed difference of statistical significance within the opinions of the study samples about the impact of consulting services on auditor independence. The study includes a number of recommendations mainly: The Ministry of Finance and the Lebanese Association of Certified Public Accountants must augment legislations related to violations and punishments against Lebanese audit firms which fail to comply with their professional duties upon providing consulting services. The Lebanese Association of Certified Public Accountants should put forth audit control to organize the actual practice of supplying consulting services by audit firms. Using the method of team auditing instead of individual auditing leads to enhancing auditor independence. Legislation related to commerce should include some articles which organize the process of changing the auditor, where essential reasons should be presented for a change. In addition, a change should not be allowed during the financial year which the auditor is auditing to protect and enhance the auditor’s independence.